2007
DOI: 10.1161/atvbaha.107.148759
|View full text |Cite
|
Sign up to set email alerts
|

Kininostatin Associates With Membrane Rafts and Inhibits αvβ3 Integrin Activation in Human Umbilical Vein Endothelial Cells

Abstract: Objective-The cleaved form of high molecular weight kininogen (HKa) is a potent inhibitor of angiogenesis and tumor growth in vivo; the functional domain has been identified as domain 5 (D5, named as kininostatin). We now identify the subcellular targeting site for D5 on endothelial cells (ECs), and investigate D5 inhibition of integrin functions. Methods and Results-Endothelial membrane rafts were isolated using sucrose density gradient centrifugation. D5, bound to ECs, was predominantly associated with membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…For example, TSP-1 induces focal adhesion dissociation through calreticulin and phosphatidylinositol 3-kinase signaling (Goicoechea et al, 2000;Orr et al, 2002). Blockade of integrin interactions with ECM ligands has been reported previously (Hadari et al, 2000;Hughes, 2001;Wu et al, 2007) as well as indirect effects on adhesion through modulation of growth factor signaling (Bornstein and Sage, 2002;Hollier et al, 2005Hollier et al, , 2008. Finally, the FN-binding properties of tenascin-C reduce cell adhesion and modify intracellular signaling by preventing syndecan-4 receptor binding to the C-terminal heparin-binding (HepII) domain of FN (Huang et al, 2001;Orend et al, 2003;Midwood et al, 2004a).…”
Section: Introductionmentioning
confidence: 63%
“…For example, TSP-1 induces focal adhesion dissociation through calreticulin and phosphatidylinositol 3-kinase signaling (Goicoechea et al, 2000;Orr et al, 2002). Blockade of integrin interactions with ECM ligands has been reported previously (Hadari et al, 2000;Hughes, 2001;Wu et al, 2007) as well as indirect effects on adhesion through modulation of growth factor signaling (Bornstein and Sage, 2002;Hollier et al, 2005Hollier et al, , 2008. Finally, the FN-binding properties of tenascin-C reduce cell adhesion and modify intracellular signaling by preventing syndecan-4 receptor binding to the C-terminal heparin-binding (HepII) domain of FN (Huang et al, 2001;Orend et al, 2003;Midwood et al, 2004a).…”
Section: Introductionmentioning
confidence: 63%
“…Spreading was performed as described (39). Briefly, hVSMC (10 5 cells/ml) were plated on glass coverslips in growth media.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the by-products of ECM digestion are frequently small, soluble ECM fragments that subsequently compete with substrate-immobilized ligand for integrin occupancy. Studies have identified a growing list of these, including angiogstatin, endostatin, kininostatin, restin, tumstatin and vastatin (O'Reilly et al, 1997;Jimenez et al, 2000;Xu et al, 2001;John et al, 2005;Chen et al, 2006;Wu et al, 2007b), and it is likely that many as yet uncharacterized fragments remain to be discovered.…”
Section: Cell Adhesion and Ecm Degradation As A Central Mechanism In mentioning
confidence: 99%